Analisis Risiko Pembangunan Kapal Menggunakan Teknik Matriks Konsekuensi-Probabilitas - Nabila Ainun Nur Rahmat; Wahyuddin Wahyuddin; Habibi Palippui (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
Shipbuilding in shipyards can’t be separated from uncertain risks that can occur, so it’s necessary to carry out a risk management analysis to minimize and take action so that risks can be avoided and overcome. Risk analysis can be carried out using consequence and probability matrix techniques, one of the risk management in SNI IEC/ISO 31010:2016 by combining the consequences and probability assessments to produce a risk level. Risk assessment is the overall process of hazard identification, risk analysis, and risk evaluation. The purpose of this study was to identify hazards in new building works and determine the magnitude of the level of consequences and probability of a risk arising by using consequence and probability matrix techniques and determining the proper risk treatment or mitigation. The benefit of this study is to find out the various hazards and risk level categories using consequence and probability matrix techniques, as well as being a reference in treating or mitigating work accident risks on new building works in shipyards. The results showed that there were 14 hazards from 3 series of activity that is plate cutting, welding, and lifting. Risk analysis is obtained from the mode or the highest value in the probability assessment with the highest mode or value in the consequence assessment based on the respondent’s answer. The risk scale from the risk analysis shows that there’s a moderate level of risk (priority III), low risk (priority IV), and very low risk (priority V) in new building work at PT. Industri Kapal Indonesia. Treatment or mitigation of risk that can be carried out is to wear PPE (Personal Protective Equipment), periodic maintenance of equipment, completing safety signs in the field, and working according to the applicable SOP (Standard Operating Procedure).